Analisis Keselamatan dan Kesehatan Kerja Rumah Sakit di Rumah Sakit Laras Simalungun Tahun 2023 - DAMAYANTI DAMAYANTI AFRIAWAN (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2023)
A hospital is a facility for the delivery of comprehensive medical services to individuals, including inpatient, outpatient, and emergency care.. Hospitals have many things that have the potential to cause hazards that can have an impact or risk to Occupational Safety and Health. For this reason, hospitals need to implement Hospital Occupational Safety and Health. In This research uses a form of qualitative research with 5 (five) informants. Data is taken from the results of the checklist of SMK3 PP Application Form No.50 of 2012. From the data, it is obtained that Laras Hospital has implemented Occupational Safety and Health with a Good Implementation Level for K3 Policy Determination where officers responsible for disaster management have been determined but have not received training, Satisfactory Implementation Level for K3 Planning where Laras Hospital has implemented all criteria, Satisfactory Implementation Level for K3 Plan Implementation even though the K3 Document at Laras Hospital does not yet have an identity status, Satisfactory Implementation Level for K3 Monitoring and Evaluation, and Good Implementation Level for K3 Performance Review and Improvement where executive management members have not attended K3 training. That way Laras Hospital has implemented Hospital Occupational Safety and Health with a Satisfactory Implementation Rate. Laras Hospital should raise the standard of human resources. to executive management members to attend K3 trainings, Laras Hospital needs to prepare K3RS facilities and infrastructure related to disasters.